Globalization and the role of public transfers in redistributing income in Latin America and the Caribbean - Emmanuel Skoufias; Kathy Lindert; Joseph Shapiro (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
This paper focuses on measuring the extent to which publicly subsidized transfers in Latin America and the Caribbean redistribute income. The redistributive power of 56 transfers in eight countries is measured by their simulated impacts on poverty and inequality, and by their distributional characteristic. Our findings suggest that public transfers can be effective instruments to redistribute income to the poor. Yet frequently they have not managed to do so. The redistributive impacts from social insurance are limited - and even regressive in some countries. This is due to two design factors: a truncation in coverage due to requirements of membership in formal labour markets which exclude the majority of the poor, and highly generous unit benefits for those in the upper quintiles. The more recent emergence of social assistance only partially offsets this historical truncation of public transfers in the region. Despite coverage and distributional patterns that favour the poor, small unit subsidies limit the redistributive, poverty and inequality impacts of even the most targeted social assistance programmes. We also find considerable variation among social assistance programmes, with many food based programmes and scholarships being regressive.
Keywords: D31; H55; I31; I38; 330; social protection; insurance; redistribution; targeting; poverty; inequality; welfare; Sozialtransfer; Einkommensumverteilung; Armut; Lateinamerika; Karibische Staaten